A nano-deposition liquid and its preparation method and application method
By using nanodeposit solution and magnetic field control methods, an insulated nanocomposite ceramic coating with high density and high electrical insulation performance was prepared, which solved the problem of low density of ceramic coatings in the prior art and achieved higher Electrical insulation and flame retardant properties.
Patent Information
- Application Number
- CN202310048195.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-01-31
AI Technical Summary
The prior art has problems of pores and low density when preparing ceramic coatings using thermal spraying technology, and the sealing agent and laser remelting treatment have poor high temperature and wear resistance, limited penetration depth, and introduction of residual stress. question.
Provide a nano-deposited liquid, made of silicon dioxide, aluminum trioxide, zirconium oxide, boron nitride, modified high-temperature epoxy resin, modified high-temperature fluororesin, inorganic organic hybrid resin, magneto-ion composite agent and other raw materials Preparation, insulated nanocomposite ceramic coatings are prepared by combining liquid phase nanodeposition and gas phase nanodeposition with magnetic field control.
The ionic density of the coating is achieved, and the geometric multiple improves the electrical insulation performance of the coating, ensures the safety, stability and reliability of the electrical insulation, and can reach the coating thickness of 30 microns withstand voltage DC of 5000 volts (DC5000V) or above, and improves the flame retardant performance. .
Smart Images

Figure BDA0004056498510000131 
Figure BDA0004056498510000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic coatings, and in particular to a nanometer deposition liquid and a preparation method and an application method thereof. Background Art
[0002] Many motors and electrical equipment are made of conductor materials, magnetic materials, insulating materials and structural materials. Except for insulating materials, the rest are metal materials, which are all conductive. During the operation of the equipment, it will inevitably be affected by temperature, current, vibration, etc., and some harmful gases, chemicals, dust and other factors will be generated. These factors have a significant impact on the insulating material, which is easy to deteriorate and deteriorate, and it is likely to damage the equipment. Therefore, the quality of the insulating material will also be related to the normal operation of the electrical equipment.
[0003] At present, copper bars used in high-power power circuits, battery shells, and electronic and electrical appliances that require partial or complete insulation are generally insulated by coating with rubber or covering with insulating film (polymer insulating film). Such a process basically involves coating with rubber or covering with insulating film first, then bending, and then bending again, which may cause damage and the risk of insulation failure.
[0004] Ceramic materials have ionic and covalent bond structures, high bond energy, strong interatomic bonding force, low surface free energy, small interatomic distance, dense stacking, and no free electron movement. These properties give ceramic materials distinctive characteristics such as high melting point, high hardness, high stiffness, high chemical stability, high insulation and thermal insulation ability, low thermal conductivity, small thermal expansion coefficient, small friction coefficient, and no ductility. The use of thermal spraying technology, especially plasma spraying technology, to prepare ceramic coatings on metal substrates can organically combine the characteristics of ceramic materials with those of metal materials to obtain composite material structures and products. However, there are problems with porosity and poor density when using thermal spraying technology to prepare ceramic coatings on the market. There are two ways to reduce the porosity of thermal sprayed ceramic coatings at home and abroad: (1) treating the prepared coating with sealing agents, laser remelting, etc. to achieve pore sealing; (2) regulating the density of the prepared coating through process optimization and ceramic coating raw material design. However, organic sealers have poor high temperature and wear resistance, inorganic sealers have limited penetration depth, and laser remelting treatment can easily introduce large residual stress in the coating, causing workpiece deformation and cladding layer cracks, resulting in a decrease in the mechanical properties of the coating. Summary of the invention
[0005] The purpose of the present invention is to provide a nanometer deposition liquid and a preparation method and an application method thereof, so as to solve the problems existing in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a nano-deposition liquid, which is prepared from the following raw materials in parts by weight: 1.8 to 18.6 parts of silicon dioxide, 0.6 to 5.2 parts of aluminum oxide, 0.2 to 3.7 parts of zirconium oxide, 0.5 to 3.2 parts of boron nitride, 1.4 to 9.8 parts of modified high-temperature epoxy resin, 0.2 to 3.6 parts of modified high-temperature fluororesin, 2.1 to 13.8 parts of inorganic-organic hybrid resin, and 0.2 to 5.6 parts of magnetic-electric ion composite agent. parts, composite wetting agent 0.05-1.2 parts, water-based film-forming aid 0.05-0.8 parts, water-based leveling aid 0.06-2.1 parts, water-based nano-dispersant 0.01-0.5 parts, water-based composite antifoaming and defoaming agent 0.01-1.9 parts, water-based rheological additive 0.02-1.1 parts, composite coupling agent 0.05-1.9 parts, water-based stabilizer 0.05-0.9 parts, inorganic color paste 2-16 parts, water 16-49 parts.
[0008] Preferably, the magneto-ionic composite agent comprises one or more of [bmim]FeCl4, [bpy]FeCl4, [bmp]FeCl4 and [pbmim](FeCl4)2;
[0009] The composite wetting agent comprises one or more of carbon fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and fatty acid polyoxyethylene ester;
[0010] The aqueous film-forming aid comprises one or more of Texanol, Coasol, DPnB, DBE-IB, Nexcoat 795, LusolvanFBH, DAL-PADC, EEH, OE400, SER-AD, FX511 and alcohol ester 12;
[0011] The aqueous leveling agent includes one or more of TEGOWET270, TEGOWET280, BYK-UV3530 and Dynol604.
[0012] Preferably, the aqueous nanodispersant comprises one or more of sodium polyacrylate, ammonium polyacrylate and sodium hexametaphosphate;
[0013] The aqueous composite antifoaming agent comprises one or more of BYK defoamer BYK-017, BYK defoamer BYK-044 and BYK defoamer BYK-019;
[0014] The aqueous rheological additive includes one or more of WT-121, SW-452, BYK346, and WT400.
[0015] Preferably, the composite coupling agent comprises one or more of an aluminum zirconium coupling agent, a silane coupling agent and a titanate coupling agent;
[0016] The aqueous stabilizer comprises one or more of SILRES MP50E and HD-020;
[0017] The inorganic color paste comprises one or more of titanium white, chrome yellow, iron blue, cadmium red, cadmium yellow, lithopone, carbon black, red iron oxide and yellow iron oxide.
[0018] The present invention also provides a method for preparing a nano-deposition liquid, comprising the following steps:
[0019] S1: Inorganic-organic hybrid resin, modified high-temperature epoxy resin, and modified high-temperature fluororesin are sequentially added to water; 5 to 30 minutes later, water-based nano-dispersant, composite wetting agent, and water-based composite antifoaming agent are sequentially added; 5 to 30 minutes later, silicon dioxide, aluminum oxide, zirconium oxide, boron nitride, inorganic color paste, and composite coupling agent are sequentially added, and static aging is performed to form a primary aging liquid;
[0020] S2: Grind and disperse the primary aging liquid, and add the aqueous nano-dispersant and aqueous composite antifoaming agent again during the process; seal and mature after the grinding to form a secondary aging liquid;
[0021] S3: The secondary aging liquid is ground and dispersed again; 5 to 30 minutes after the grinding is completed, an aqueous film-forming agent, an aqueous leveling agent, an aqueous rheological agent, an aqueous stabilizer, and a magnetic ion composite agent are sequentially added for static aging to form a tertiary aging liquid to obtain a nano-deposition liquid.
[0022] Preferably, the static aging time in step S1 is 12 to 48 hours;
[0023] The grinding and dispersion temperature in step S2 is 5 to 25° C.; the average particle size D50 of the grinding and dispersion is 0.05 to 5 μm; and the sealing and aging time is 12 to 48 hours;
[0024] The grinding and dispersion temperature in step S3 is 5 to 25° C.; the average particle size D50 of the grinding and dispersion is 0.05 to 5 μm; and the static aging time is 12 to 48 hours.
[0025] Preferably, the mass ratio of the aqueous nano-dispersant in step S1 to the aqueous nano-dispersant in step S2 is 1 to 2:1;
[0026] The mass ratio of the aqueous composite antifoaming and defoaming agent in step S1 to the aqueous composite antifoaming and defoaming agent in step S2 is 1 to 2:1.
[0027] The present invention also provides a method for preparing an insulating nano-composite ceramic coating workpiece using a nano-deposition liquid, comprising the following steps:
[0028] S1: performing magnetization pretreatment on the workpiece under normal temperature and pressure to obtain a pretreated workpiece;
[0029] S2: Under the condition of matching magnetic field control, the obtained pre-treated workpiece is subjected to liquid phase nano-deposition in a nano-deposition liquid to obtain a workpiece with a nano-deposition insulating nano-composite ceramic coating;
[0030] S3: Under the condition of matching magnetic field control, the workpiece with the nano-deposited insulating nano-composite ceramic coating is subjected to impurity removal treatment in a circulating liquid to obtain a workpiece with the nano-deposited insulating nano-composite ceramic coating controlled by a magnetic field;
[0031] S4: Under the condition of matching magnetic field control, the obtained magnetic field controlled insulating nano-composite ceramic coating workpiece is heated at normal pressure for rearrangement and densification to obtain a rearranged and densified insulating nano-composite ceramic coating workpiece;
[0032] S5: Under the conditions of normal pressure, heating and matching magnetic field control, a protective atmosphere is introduced to perform gas phase nano-deposition on the obtained rearranged and densified insulating nano-composite ceramic coating workpiece to obtain an insulating nano-composite ceramic coating workpiece.
[0033] Preferably, the magnetization pretreatment in step S1 refers to magnetizing the workpiece using a magnetizer under the conditions of a magnetization voltage of 50 to 1000 V and a magnetization time of 1 to 10 s;
[0034] The matching magnetic field control in step S2 refers to the matching of the magnetic field of the nano-deposition liquid with the magnetic field of the pre-treated workpiece; the magnetic field force of the matching magnetic field is 0.8 to 7200N, and the time is 1 to 5 hours;
[0035] The magnetic field force of the matching magnetic field in step S3 is 0.8 to 7200 N, and the time is 10 to 60 minutes; the circulating fluid is water;
[0036] The magnetic field force of the matching magnetic field in step S4 is 0.8-7200N, and the time is 1-3h; the heating temperature is 45-280°C; the moisture content of the rearranged densified insulating nanocomposite ceramic coating is ≤5%;
[0037] The magnetic field force of the matching magnetic field in step S5 is 0.8-7200N, and the time is 0.5-2h; the heating temperature is 45-280°C.
[0038] The present invention provides a nano-deposition liquid, and the pre-treated workpiece after magnetization pre-treatment is subjected to liquid phase deposition reaction in the nano-deposition liquid, so that a stable and uniform insulating nano-composite ceramic coating tending to be oriented is formed on the surface of the workpiece, and the workpiece of the insulating nano-composite ceramic coating is decontaminated and rearranged and densified under the condition of matching magnetic field control, so as to further improve the density of the coating and obtain a rearranged and densified insulating nano-composite ceramic coating; the rearranged and densified insulating nano-composite ceramic coating workpiece is subjected to gas phase nano-deposition under the action of a matching magnetic field, and the workpiece is strongly arranged again for complete cross-linking and densification, so as to repair the defects of the liquid phase nano-deposition coating and ensure uniformity, and at the same time, the liquid phase deposited insulating nano-composite ceramic units are arranged again for directional purpose, so as to achieve complete densification of the insulating nano-composite ceramic coating. The present invention uses the overall technical scheme of nano-deposition liquid combined with liquid phase nano-deposition combined with gas phase nano-deposition rearrangement, so that the insulating nano-composite ceramic coating reaches ionic level density and geometrically improves the performance of electrical insulation and corrosion protection.
[0039] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0040] The insulating nanocomposite ceramic coating prepared by the nano-deposition liquid of the present invention is dense at the ion level, and the electrical insulation performance of the coating is improved geometrically; the microscopic nanocomposite ceramic particles of the coating tend to be arranged in a directional manner, which effectively improves the electrical insulation performance of the coating; the magnetic field control (non-human control) makes the coating thickness uniform and fully covered, ensuring the safety, stability and reliability of electrical insulation, and can achieve thinner coatings with higher electrical insulation performance, specifically, the coating thickness can reach 30 microns and withstand voltage of DC 5000 volts (DC5000V) or more; the insulating nanocomposite ceramic coating can be applied to copper bars for high-power power supply circuits, battery shells, electronic appliances that require partial or full insulation, new energy batteries or energy storage batteries, etc. Since the coating is a composite ceramic, the flame retardant performance is better and can reach the flame retardant V0 level; stable and high-strength electrical insulation can be achieved on the surface of complex device products; the high purity of the coating components is achieved by removing impurities through magnetic field control (non-human control), and the stability, safety and reliability of electrical insulation are also ensured. DETAILED DESCRIPTION
[0041] The present invention provides a nano-deposition liquid, which is prepared from the following raw materials in parts by weight: 1.8 to 18.6 parts of silicon dioxide, 0.6 to 5.2 parts of aluminum oxide, 0.2 to 3.7 parts of zirconium oxide, 0.5 to 3.2 parts of boron nitride, 1.4 to 9.8 parts of modified high-temperature epoxy resin, 0.2 to 3.6 parts of modified high-temperature fluororesin, 2.1 to 13.8 parts of inorganic-organic hybrid resin, and 0.2 to 5.6 parts of magnetic-electric ion composite agent. parts, composite wetting agent 0.05-1.2 parts, water-based film-forming aid 0.05-0.8 parts, water-based leveling aid 0.06-2.1 parts, water-based nano-dispersant 0.01-0.5 parts, water-based composite antifoaming and defoaming agent 0.01-1.9 parts, water-based rheological additive 0.02-1.1 parts, composite coupling agent 0.05-1.9 parts, water-based stabilizer 0.05-0.9 parts, inorganic color paste 2-16 parts, water 16-49 parts.
[0042] In the present invention, the silicon dioxide is 1.8 to 18.6 parts, preferably 5 to 15 parts, and more preferably 8 to 12 parts; the particle size of the silicon dioxide is 1 to 100 nm, preferably 20 to 80 nm, and more preferably 35 to 50 nm;
[0043] The aluminum oxide is 0.6 to 5.2 parts, preferably 1.5 to 4 parts, and more preferably 2 to 3.6 parts; the particle size of the aluminum oxide is 10 to 100 nm, preferably 30 to 60 nm;
[0044] The zirconium oxide is 0.2 to 3.7 parts, preferably 1.8 to 2.9 parts; the particle size of the zirconium oxide is 0.5 to 5 nm, preferably 2 to 4 nm;
[0045] The boron nitride is 0.5 to 3.2 parts, preferably 1 to 3 parts.
[0046] In the present invention, the modified high temperature epoxy resin is 1.4 to 9.8 parts, preferably 3 to 7.6 parts, and more preferably 4.5 to 6 parts; the modified high temperature epoxy resin is preferably a modified high temperature epoxy resin of model YS-616 produced by Jinan Yisheng Resin Co., Ltd.;
[0047] The modified high temperature fluororesin is 0.2 to 3.6 parts, preferably 1 to 2.4 parts; the modified high temperature fluororesin is preferably a modified high temperature fluororesin of model PFAAP-231SH produced by Daikin Corporation of Japan;
[0048] The inorganic-organic hybrid resin is 2.1 to 13.8 parts, preferably 5.6 to 11.4 parts, and more preferably 7.2 to 9.6 parts; the inorganic-organic hybrid resin is an organic-inorganic hybrid water-based silicone resin with model number W130 produced by Shuangxin Water-based Materials Co., Ltd.
[0049] In the present invention, the magneto-ionic composite agent is 0.2 to 5.6 parts, preferably 1 to 3 parts; the magneto-ionic composite agent comprises one or more of [bmim]FeCl4, [bpy]FeCl4, [bmp]FeCl4 and [pbmim](FeCl4)2, preferably one or more of [bmim]FeCl4, [bpy]FeCl4 and [bmp]FeCl4;
[0050] The composite wetting agent is 0.05 to 1.2 parts, preferably 0.3 to 0.9 parts; the composite wetting agent comprises one or more of carbon aliphatic alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and fatty acid polyoxyethylene ester, preferably one or more of carbon aliphatic alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether;
[0051] The aqueous film-forming aid is 0.05 to 0.8 parts, preferably 0.2 to 0.6 parts; the aqueous film-forming aid comprises one or more of Texanol, Coasol, DPnB, DBE-IB, Nexcoat 795, LusolvanFBH, DAL-PADC, EEH, OE400, SER-AD, FX511 and alcohol ester 12, preferably one or more of Texanol, Coasol, DPnB, DBE-IB, Nexcoat 795 and LusolvanFBH;
[0052] The aqueous leveling agent is 0.06 to 2.1 parts, preferably 0.76 to 1.8 parts; the aqueous leveling agent includes one or more of TEGOWET270, TEGOWET280, BYK-UV3530 and Dynol604, preferably one or more of TEGOWET270, TEGOWET280 and BYK-UV3530.
[0053] In the present invention, the aqueous nano-dispersant is 0.01 to 0.5 parts, preferably 0.15 to 0.38 parts; the aqueous nano-dispersant comprises one or more of sodium polyacrylate, ammonium polyacrylate and sodium hexametaphosphate, preferably one or more of sodium polyacrylate and ammonium polyacrylate;
[0054] The aqueous composite antifoaming agent is 0.01 to 1.9 parts, preferably 0.26 to 1.4 parts; the aqueous composite antifoaming agent comprises one or more of BYK defoamer BYK-017, BYK defoamer BYK-044 and BYK defoamer BYK-019, preferably one or more of BYK defoamer BYK-017 and BYK defoamer BYK-044;
[0055] The aqueous rheological additive is 0.02 to 1.1 parts, preferably 0.5 to 0.9 parts; the aqueous rheological additive comprises one or more of WT-121, SW-452, BYK346, and WT400, preferably one or more of WT-121, SW-452, and BYK346.
[0056] In the present invention, the composite coupling agent is 0.05 to 1.9 parts, preferably 0.4 to 1.1 parts; the composite coupling agent comprises one or more of an aluminum zirconium coupling agent, a silane coupling agent and a titanate coupling agent, preferably a silane coupling agent;
[0057] The aqueous stabilizer is 0.05 to 0.9 parts, preferably 0.2 to 0.6 parts; the aqueous stabilizer comprises one or more of SILRES MP50E and HD-020, preferably SILRES MP50E;
[0058] The inorganic color paste is 2 to 16 parts, preferably 5 to 10 parts, and more preferably 6 to 8 parts; the particle size of the inorganic color paste is 10 to 40 nm, preferably 20 to 30 nm; the inorganic color paste includes one or more of titanium white, chrome yellow, iron blue, cadmium red, cadmium yellow, lithopone, carbon black, iron oxide red and iron oxide yellow, selected according to the coating color requirements;
[0059] The water is 16 to 49 parts, preferably 20 to 40 parts.
[0060] The present invention also provides a method for preparing a nano-deposition liquid, comprising the following steps:
[0061] S1: Inorganic-organic hybrid resin, modified high-temperature epoxy resin, and modified high-temperature fluororesin are sequentially added to water; 5 to 30 minutes later, water-based nano-dispersant, composite wetting agent, and water-based composite antifoaming agent are sequentially added; 5 to 30 minutes later, silicon dioxide, aluminum oxide, zirconium oxide, boron nitride, inorganic color paste, and composite coupling agent are sequentially added, and static aging is performed to form a primary aging liquid;
[0062] S2: Grind and disperse the primary aging liquid, and add the aqueous nano-dispersant and aqueous composite antifoaming agent again during the process; seal and mature after the grinding to form a secondary aging liquid;
[0063] S3: The secondary aging liquid is ground and dispersed again; 5 to 30 minutes after the grinding is completed, an aqueous film-forming agent, an aqueous leveling agent, an aqueous rheological agent, an aqueous stabilizer, and a magnetic ion composite agent are sequentially added for static aging to form a tertiary aging liquid to obtain a nano-deposition liquid.
[0064] In the present invention, in step S1, the aqueous nano-dispersant, the composite wetting agent, and the aqueous composite antifoaming agent are added under slow stirring for 5 to 30 minutes, preferably 10 to 20 minutes, and the mixture is stirred and mixed evenly; the stirring rate of the slow stirring is 30 to 80 r / min, preferably 45 to 70 r / min;
[0065] In the step S1, silicon dioxide, aluminum oxide, zirconium oxide, boron nitride, inorganic color paste, and composite coupling agent are added at intervals of 5 to 30 minutes, preferably 10 to 20 minutes, under slow stirring; the stirring rate of the slow stirring is 30 to 80 r / min, preferably 45 to 70 r / min;
[0066] After adding silicon dioxide, aluminum oxide, zirconium oxide, boron nitride, inorganic color paste and composite coupling agent in step S1, high-speed stirring is performed to disperse them uniformly; the high-speed stirring rate is 500 to 2000 r / min; preferably 800 to 1500 r / min;
[0067] The static aging time in step S1 is 12 to 48 hours, preferably 14 to 23 hours;
[0068] The grinding and dispersion temperature in step S2 is 5 to 25° C., preferably 15 to 20° C.; the average particle size D50 of the grinding and dispersion is 0.05 to 5 μm, preferably 0.6 to 3 μm, and more preferably 1 to 2 μm;
[0069] The sealing and aging time in step S2 is 12 to 48 hours, preferably 15 to 30 hours.
[0070] In the present invention, the mass ratio of the aqueous nanodispersant in step S1 to the aqueous nanodispersant in step S2 is 1 to 2:1, preferably 1.2 to 1.6:1;
[0071] The mass ratio of the aqueous composite antifoaming agent in step S1 to the aqueous composite antifoaming agent in step S2 is 1 to 2:1, preferably 1.2 to 1.6:1.
[0072] In the present invention, the grinding and dispersion temperature in step S3 is 5 to 25° C., preferably 15 to 20° C.; the average particle size D50 of the grinding and dispersion is 0.05 to 5 μm, preferably 0.2 to 2.4 μm, and more preferably 0.8 to 1.7 μm;
[0073] In the step S3, under the condition of slow stirring, the aqueous film-forming agent, aqueous leveling agent, aqueous rheological agent, aqueous stabilizer and magnetic ion composite agent are added at intervals of 5 to 30 minutes, preferably 15 to 20 minutes; the slow stirring rate is 30 to 80 r / min, preferably 45 to 70 r / min;
[0074] The static aging time in step S3 is 12 to 48 hours, preferably 20 to 40 hours.
[0075] The present invention also provides a method for preparing an insulating nano-composite ceramic coating workpiece using a nano-deposition liquid, comprising the following steps:
[0076] S1: performing magnetization pretreatment on the workpiece under normal temperature and pressure to obtain a pretreated workpiece;
[0077] S2: Under the condition of matching magnetic field control, the obtained pre-treated workpiece is subjected to liquid phase nano-deposition in a nano-deposition liquid to obtain a workpiece with a nano-deposition insulating nano-composite ceramic coating;
[0078] S3: Under the condition of matching magnetic field control, the workpiece with the nano-deposited insulating nano-composite ceramic coating is subjected to impurity removal treatment in a circulating liquid to obtain a workpiece with the nano-deposited insulating nano-composite ceramic coating controlled by a magnetic field;
[0079] S4: Under the condition of matching magnetic field control, the obtained magnetic field controlled insulating nano-composite ceramic coating workpiece is heated at normal pressure for rearrangement and densification to obtain a rearranged and densified insulating nano-composite ceramic coating workpiece;
[0080] S5: Under the conditions of normal pressure, heating and matching magnetic field control, a protective atmosphere is introduced to perform gas phase nano-deposition on the obtained rearranged and densified insulating nano-composite ceramic coating workpiece to obtain an insulating nano-composite ceramic coating workpiece.
[0081] In the present invention, the magnetization pretreatment in step S1 refers to magnetizing the workpiece using a magnetizer under the conditions of a magnetizing voltage of 50 to 1000 V, preferably 200 to 800 V, a magnetizing time of 1 to 10 s, preferably 3 to 6 s; the normal temperature is 5 to 40° C., preferably 26 to 35° C.;
[0082] The matching magnetic field control in step S2 refers to matching the magnetic field of the nano-deposition liquid with the magnetic field of the pre-treated workpiece; the magnetic field force of the matching magnetic field is 0.8 to 7200N, preferably 100 to 6500N, more preferably 1000 to 5000N, and more preferably 2500 to 4000N; the time is 1 to 5 hours, preferably 2 to 4 hours;
[0083] The magnetic field force of the matching magnetic field in step S3 is 0.8 to 7200 N, more preferably 1000 to 5000 N, and more preferably 2500 to 4000 N; the time is 10 to 60 min, preferably 20 to 40 min; the circulating fluid is water;
[0084] The impurity removal treatment in step S3 refers to removing uncontrolled deposited ions and other impurities in the workpiece of the nano-deposited insulating composite ceramic coating;
[0085] The magnetic field force of the matching magnetic field in step S4 is 0.8-7200N, more preferably 1000-5000N, and more preferably 2500-4000N; the time is 1-3h, preferably 1.5-2.3h; the heating temperature is 45-280°C, preferably 100-250°C; the moisture content of the rearranged densified insulating nanocomposite ceramic coating is ≤5%, preferably ≤3%;
[0086] The magnetic field force of the matching magnetic field in step S5 is 0.8 to 7200 N, more preferably 1000 to 5000 N, and more preferably 2500 to 4000 N; the time is 0.5 to 2 hours, preferably 1 to 1.8 hours; the heating temperature is 45 to 280° C., preferably 100 to 250° C.;
[0087] The vapor deposition reaction in step S5 is carried out under a protective atmosphere; the protective atmosphere is preferably argon.
[0088] In the present invention, the workpieces include power copper bars, battery shells, electrical and electronic components that require ultra-thin insulation; refrigeration and heating equipment components such as evaporators, condensers, radiators, plate heat exchangers, shell and tube heat exchangers, finned tubes; magnesium alloy components such as laptop computer shells, mobile phone shells, monitoring shells, drone components, aerospace components; neodymium iron boron such as permanent magnet motors, magnetic separation equipment; silicon steel sheets such as iron cores, rotors, stators, transformers, motors; fasteners such as threaded structural parts; instruments and accessories for marine engineering environments, refineries, power plants and mining equipment; chemical equipment and high-demand outdoor equipment environments.
[0089] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0090] Example 1
[0091] Preparation of nano-deposition solution:
[0092] S1: 2.1 parts of W130, 5.4 parts of YS-616, and 1.2 parts of PFAAP-231SH were sequentially added to 16 parts of water, and stirred evenly at a stirring rate of 30 r / min; after continuing to stir for 5 minutes, 0.3 parts of sodium polyacrylate, 0.1 parts of carbon fatty alcohol polyoxyethylene ether, and 1 part of BYK defoamer BYK-019 were sequentially added, and stirred evenly at a stirring rate of 30 r / min; after continuing to stir for 5 minutes, 10.6 parts of silicon dioxide, 3.4 parts of aluminum oxide, 0.2 parts of zirconium oxide, 1.4 parts of boron nitride, 12 parts of titanium dioxide, and 0.17 parts of aluminum zirconium coupling agent were sequentially added, and stirred and dispersed evenly at a stirring rate of 500 r / min, and statically aged for 12 hours to form a primary aged liquid;
[0093] S2: The primary aging liquid is vacuum pumped into the nano-grinding and dispersing system, and nano-grinded and dispersed at 10°C under normal pressure. During this period, 0.15 parts of sodium polyacrylate and 0.5 parts of BYK defoamer BYK-019 are added again; after grinding to 0.06 μm, the liquid is sealed and aged for 16 hours to form a secondary aging liquid;
[0094] S3: The secondary aging liquid is vacuum pumped into the nano-grinding and dispersing system again; nano-grinding and dispersing at 5°C and normal pressure to 0.05μm; after an interval of 5 minutes, 0.4 parts of Texanol, 0.06 parts of BYK-UV3530, 0.02 parts of WT-121, 0.05 parts of HD-020, and 0.6 parts of [bmim]FeCl4 are added in sequence at room temperature and pressure with a stirring rate of 30r / min, and stirred evenly, and statically aged for 20h to form a tertiary aging liquid to obtain a nano-deposition liquid.
[0095] Preparation of insulating nanocomposite ceramic coating workpieces using nano-deposition liquid:
[0096] S1: Under normal temperature and pressure, the battery shell to be insulated is subjected to magnetization pretreatment using a magnetizer at a magnetizing voltage of 200 V and a magnetizing time of 5 s to obtain a pretreated battery shell;
[0097] S2: placing the obtained pretreated battery shell in a nano-deposition liquid, adjusting the magnetic field of the nano-deposition liquid to match the magnetic field of the pre-treated battery shell, controlling the magnetic field force of the matching magnetic field to be 25N to achieve liquid phase deposition of the nano-deposition liquid, and obtaining a battery shell with a nano-deposition insulating nano-composite ceramic coating after 3 hours;
[0098] S3: The battery shell of nano-deposited insulating nano-composite ceramic coating is decontaminated in a normal temperature and pressure aqueous solution (circulated) controlled by a matching magnetic field of 25N for 30 minutes to form a nano-deposited insulating nano-composite ceramic coating battery shell controlled by a magnetic field;
[0099] S4: Under the condition of a matching magnetic field of 25N, the obtained magnetic field-controlled insulating nano-composite ceramic coating workpiece is heated to 200°C at normal pressure for rearrangement and densification for 1 hour to obtain a rearranged and densified insulating nano-composite ceramic coating battery shell with a moisture content of 3%;
[0100] S5: The rearranged and densified insulating nano-composite ceramic coating battery shell is subjected to vapor phase nano-deposition for 1 hour under the conditions of a matching magnetic field of 25N, normal pressure and a temperature of 280°C, thereby obtaining an insulating nano-composite ceramic coating battery shell.
[0101] Example 2
[0102] Preparation of nano-deposition solution:
[0103] S1: 13.8 parts of W130, 1.4 parts of YS-616, and 3.6 parts of PFAAP-231SH were sequentially added to 36 parts of water, and stirred evenly at a stirring rate of 50 r / min; after continuing to stir for 20 minutes, 0.4 parts of ammonium polyacrylate, 0.05 parts of alkylphenol polyoxyethylene ether, and 1.2 parts of BYK defoamer BYK-044 were sequentially added, and stirred evenly at a stirring rate of 50 r / min; after continuing to stir for 15 minutes, 1.8 parts of silicon dioxide, 5.2 parts of aluminum oxide, 3.7 parts of zirconium oxide, 3.2 parts of boron nitride, 2 parts of titanium dioxide, and 0.05 parts of silane coupling agent were sequentially added, and stirred and dispersed evenly at a stirring rate of 1500 r / min, and statically aged for 24 hours to form a primary aged liquid;
[0104] S2: The primary aging liquid is vacuum pumped into the nano-grinding and dispersing system, and nano-grinded and dispersed at 5°C under normal pressure. During this period, 0.2 parts of aqueous nano-dispersant and 0.6 parts of aqueous composite antifoaming and defoaming agent are added again; after grinding to 1 μm, the liquid is sealed and aged for 16 hours to form a secondary aging liquid;
[0105] S3: The secondary aging liquid is vacuum pumped into the nano-grinding and dispersing system again; nano-grinding and dispersing at 5°C and normal pressure to 0.4μm; after an interval of 20 minutes, 0.05 parts of Coasol, 2.1 parts of TEGOWet280, 1.1 parts of SW-452, 0.4 parts of HD-020, and 0.2 parts of [bpy]FeCl4 are added in sequence at room temperature and pressure with a stirring rate of 50r / min, and stirred evenly, and statically aged for 12h to form a tertiary aging liquid to obtain a nano-deposition liquid.
[0106] Preparation of insulating nanocomposite ceramic coating workpieces using nano-deposition liquid:
[0107] S1: Under normal temperature and pressure, the battery shell to be insulated is subjected to magnetization pretreatment using a magnetizer at a magnetizing voltage of 200 V and a magnetizing time of 5 s to obtain a pretreated battery shell;
[0108] S2: placing the obtained pre-treated battery shell in a nano-deposition liquid, adjusting the magnetic field of the nano-deposition liquid to match the magnetic field of the pre-treated battery shell, controlling the magnetic field force of the matching magnetic field to be 25N to achieve liquid phase deposition of the nano-deposition liquid, and obtaining a battery shell with a nano-deposition insulating nano-composite ceramic coating after 4 hours;
[0109] S3: The battery shell of nano-deposited insulating nano-composite ceramic coating is removed from impurities in a normal temperature and pressure aqueous solution (circulated) controlled by a matching magnetic field of 25N for 50 minutes to form a nano-deposited insulating nano-composite ceramic coating battery shell controlled by a magnetic field;
[0110] S4: Under the condition of a matching magnetic field of 25N, the obtained magnetic field-controlled insulating nano-composite ceramic coating workpiece is heated to 230°C at normal pressure for rearrangement and densification for 2 hours to obtain a rearranged and densified insulating nano-composite ceramic coating battery shell with a moisture content of 3%;
[0111] S5: The rearranged and densified insulating nano-composite ceramic coating battery shell is subjected to vapor phase nano-deposition for 1 hour under the conditions of a matching magnetic field of 25N, normal pressure and a temperature of 280°C, thereby obtaining an insulating nano-composite ceramic coating battery shell.
[0112] Example 3
[0113] Preparation of nano-deposition solution:
[0114] S1: Add 10.1 parts of W130, 9.8 parts of YS-616, and 0.2 parts of PFAAP-231SH to 49 parts of water, and stir evenly at a stirring rate of 60 r / min; continue stirring for 30 minutes, then add 0.2 parts of sodium hexametaphosphate, 1.2 parts of alkylphenol polyoxyethylene ether, and 0.6 parts of BYK defoamer BYK-017, and stir evenly at a stirring rate of 60 r / min; continue stirring for 30 minutes, then add 18.6 parts of silicon dioxide, 0.6 parts of aluminum oxide, 2.7 parts of zirconium oxide, 1.6 parts of boron nitride, 16 parts of titanium dioxide, and 1.9 parts of titanate coupling agent, and stir and disperse evenly at a stirring rate of 2000 r / min, and statically mature for 12 hours to form a primary matured liquid;
[0115] S2: The primary aging liquid is vacuum pumped into the nano-grinding and dispersing system, and nano-grinded and dispersed at 25°C and normal pressure. During this period, 0.2 parts of sodium hexametaphosphate and 0.6 parts of BYK defoamer BYK-017 are added again; after grinding to 5μm, the liquid is sealed and aged for 20 hours to form a secondary aging liquid;
[0116] S3: The secondary aging liquid is vacuum pumped into the nano-grinding and dispersing system again; nano-grinding and dispersing at 5°C and normal pressure, grinding and dispersing to 2μm; after an interval of 30 minutes, at room temperature and pressure, with a stirring rate of 30r / min, 0.8 parts of DPnB, 1.7 parts of TEGOWet270, 0.7 parts of BYK346, 0.9 parts of SILRES MP50E, and 5.6 parts of [bmp]FeCl4 are added in sequence, stirred evenly, and statically aged for 48h to form a tertiary aging liquid to obtain a nano-deposition liquid.
[0117] Preparation of insulating nanocomposite ceramic coating workpieces using nano-deposition liquid:
[0118] S1: Under normal temperature and pressure, the copper busbar to be insulated is subjected to magnetization pretreatment using a magnetizer at a magnetizing voltage of 1000V and a magnetizing time of 10s to obtain a pretreated copper busbar;
[0119] S2: placing the obtained pretreated copper bus in a nano-deposition liquid, adjusting the magnetic field of the nano-deposition liquid to match the magnetic field of the pre-treated copper bus, controlling the magnetic field force of the matching magnetic field to be 2500N to achieve liquid phase deposition of the nano-deposition liquid, and obtaining a copper bus with a nano-deposition insulating nano-composite ceramic coating after 5 hours;
[0120] S3: The copper busbar with nano-deposition insulating nano-composite ceramic coating is removed for 60 minutes in a normal temperature and pressure aqueous solution (circulated) controlled by a matching magnetic field of 2500N to form a copper busbar with nano-deposition insulating nano-composite ceramic coating controlled by a magnetic field;
[0121] S4: Under the condition of a matching magnetic field of 2500N, the obtained magnetic field-controlled insulating nano-composite ceramic coating workpiece is heated to 280°C at normal pressure for rearrangement and densification for 3 hours to obtain a rearranged and densified insulating nano-composite ceramic coating battery shell with a moisture content of 4%;
[0122] S5: The rearranged and densified insulating nano-composite ceramic coated copper busbar is subjected to vapor phase nano-deposition for 2 hours under the conditions of a matching magnetic field of 2500N, normal pressure and a temperature of 280°C, thereby obtaining an insulating nano-composite ceramic coated copper busbar.
[0123] The performance test of the insulating nanocomposite ceramic coating obtained in Examples 1-3 is shown in Table 1
[0124] Table 1 Insulation nanocomposite ceramic coating performance test
[0125]
[0126]
[0127] It can be seen from the above embodiments that the insulating nano-composite ceramic coating prepared by the nano-deposition liquid of the present invention is dense at the ion level, and the electrical insulation performance of the coating is improved geometrically; the magnetic field control (not human control) makes the coating thickness uniform and fully covered, ensuring the safety, stability and reliability of electrical insulation, and can achieve thinner coatings with higher electrical insulation performance, specifically, the coating thickness can reach 30 microns and a withstand voltage of DC 5000 volts (DC5000V) or more; because the coating is a composite ceramic, the flame retardant performance is better, and can reach the flame retardant V0 level; stable and high-strength electrical insulation can be achieved on the surface of complex device-shaped products; the impurities are removed by magnetic field control (not human control) to achieve high purity of coating components, and the stability, safety and reliability of electrical insulation are also ensured.
[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A nano-deposition liquid, characterized in that: The invention is prepared from the following raw materials in parts by weight: 1.8-18.6 parts of silicon dioxide, 0.6-5.2 parts of aluminum oxide, 0.2-3.7 parts of zirconium oxide, 0.5-3.2 parts of boron nitride, 1.4-9.8 parts of modified high-temperature epoxy resin, 0.2-3.6 parts of modified high-temperature fluororesin, 2.1-13.8 parts of inorganic-organic hybrid resin, 0.2-5.6 parts of magnetic-electric ion composite agent, and composite wetting agent. 0.05~1.2 parts, water-based film-forming aid 0.05~0.8 parts, water-based leveling aid 0.06~2.1 parts, water-based nano-dispersant 0.01-0.5 parts, water-based composite antifoaming agent 0.01~1.9 parts, water-based rheological additive 0.02~1.1 parts, composite coupling agent 0.05~1.9 parts, water-based stabilizer 0.05~0.9 parts, inorganic color paste 2~16 parts, water 16~49 parts; The magnetic electric ion composite agent comprises one or more of [bmim]FeCl4, [bpy]FeCl4, [bmp]FeCl4 and [pbmim](FeCl4)2; The aqueous stabilizer comprises one or more of SILRES MP50E and HD-020.
2. The nano-deposition liquid according to claim 1, characterized in that The composite wetting agent comprises one or more of aliphatic alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and fatty acid polyoxyethylene ester; The aqueous film-forming aid comprises one or more of Texanol, Coasol, DPnB, DBE-IB, Nexcoat 795, LusolvanFBH, DAL-PADC, EEH, OE400, SER-AD, FX511 and alcohol ester 12; The aqueous leveling agent includes one or more of TEGOWET270, TEGOWET280, BYK-UV3530 and Dynol604.
3. The nano-deposition liquid according to claim 1 or 2, characterized in that: The aqueous nano-dispersant comprises one or more of sodium polyacrylate, ammonium polyacrylate and sodium hexametaphosphate; The aqueous composite antifoaming agent comprises one or more of BYK defoamer BYK-017, BYK defoamer BYK-044 and BYK defoamer BYK-019; The aqueous rheological additive includes one or more of WT-121, SW-452, BYK346, and WT400.
4. The nano-deposition liquid according to claim 3, characterized in that: The composite coupling agent comprises one or more of an aluminum-zirconium coupling agent, a silane coupling agent and a titanate coupling agent; The inorganic color paste comprises one or more of titanium white, chrome yellow, iron blue, cadmium red, cadmium yellow, lithopone, carbon black, iron oxide red and iron oxide yellow.
5. The method for preparing the nano-deposition liquid according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Inorganic-organic hybrid resin, modified high-temperature epoxy resin, and modified high-temperature fluororesin are sequentially added to water; 5 to 30 minutes later, water-based nano-dispersant, composite wetting agent, and water-based composite antifoaming agent are sequentially added; 5 to 30 minutes later, silicon dioxide, aluminum oxide, zirconium oxide, boron nitride, inorganic color paste, and composite coupling agent are sequentially added, and static aging is performed to form a primary aging liquid; S2: Grind and disperse the primary aging liquid, and add the aqueous nano-dispersant and aqueous composite antifoaming agent again during the process; seal and mature after the grinding to form a secondary aging liquid; S3: The secondary aging liquid is ground and dispersed again; 5 to 30 minutes after the grinding, an aqueous film-forming agent, an aqueous leveling agent, an aqueous rheological agent, an aqueous stabilizer, and a magnetic ion composite agent are sequentially added for static aging to form a tertiary aging liquid to obtain a nano-deposition liquid.
6. The method for preparing the nano-deposition liquid according to claim 5, characterized in that: The static aging time in step S1 is 12 to 48 hours; The grinding and dispersion temperature in step S2 is 5-25°C; the average particle size D50 of the grinding and dispersion is 0.05-5 μm; the sealing and aging time is 12-48 hours; The grinding and dispersion temperature in step S3 is 5-25° C.; the average particle size D50 of the grinding and dispersion is 0.05-5 μm; and the static aging time is 12-48 hours.
7. The method for preparing the nano-deposition liquid according to claim 5 or 6, characterized in that: The mass ratio of the aqueous nanodispersant in step S1 to the aqueous nanodispersant in step S2 is 1-2:1; The mass ratio of the aqueous composite antifoaming and defoaming agent in step S1 to the aqueous composite antifoaming and defoaming agent in step S2 is 1-2:
1.
8. A method for preparing an insulating nanocomposite ceramic coating workpiece using the nano deposition liquid according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: performing magnetization pretreatment on the workpiece under normal temperature and pressure to obtain a pretreated workpiece; S2: Under the condition of matching magnetic field control, the obtained pre-treated workpiece is subjected to liquid phase nano-deposition in a nano-deposition liquid to obtain a workpiece with a nano-deposition insulating nano-composite ceramic coating; S3: Under the condition of matching magnetic field control, the workpiece with the nano-deposited insulating nano-composite ceramic coating is subjected to impurity removal treatment in a circulating liquid to obtain a workpiece with the nano-deposited insulating nano-composite ceramic coating controlled by a magnetic field; S4: Under the condition of matching magnetic field control, the obtained magnetic field controlled insulating nano-composite ceramic coating workpiece is heated at normal pressure for rearrangement and densification to obtain a rearranged and densified insulating nano-composite ceramic coating workpiece; S5: Under the conditions of normal pressure, heating and matching magnetic field control, a protective atmosphere is introduced to perform gas phase nano-deposition on the obtained rearranged and densified insulating nano-composite ceramic coating workpiece to obtain an insulating nano-composite ceramic coating workpiece.
9. The method for preparing an insulating nanocomposite ceramic coating workpiece using a nano-deposition liquid according to claim 8, characterized in that: The magnetization pretreatment in step S1 refers to magnetizing the workpiece using a magnetizer under the conditions of a magnetizing voltage of 50-1000V and a magnetizing time of 1-10s; The matching magnetic field control in step S2 refers to the matching of the magnetic field of the nano-deposition liquid with the magnetic field of the pre-treated workpiece; the magnetic field force of the matching magnetic field is 0.8~7200N, and the time is 1~5h; The magnetic field force of the matching magnetic field in step S3 is 0.8-7200N, and the time is 10-60min; the circulating fluid is water; The magnetic field force of the matching magnetic field in step S4 is 0.8-7200N, and the time is 1-3h; the heating temperature is 45-280°C; the moisture content of the rearranged densified insulating nanocomposite ceramic coating is ≤5%; The magnetic field force of the matching magnetic field in step S5 is 0.8-7200N, and the time is 0.5-2h; the heating temperature is 45-280°C.
Citation Information
Patent Citations
Method for improving corrosion resistance through nano-deposition graphene composite nano-ceramic coating
CN113061961A